Konsep Persaudaraan Dalam Al-Qur`an - Ahmad Miftahusolih; Heggy Fajrianto; Taufik CH (ZAD Al-Mufassirin, 2021)
The goal to achieve in this study is: to get to know the problems faced by people in the field of brotherhood commonly known as Ukhuwah Islamiyyah. Metode yang digunakan adalah kualitatif dengan teknik meneliti dari ayat-ayat yang tercantum di dalam Al-Qur’an dan dari kitab tafsirnya yang berkaitan dengan Ukhuwwah Islamiyyah. This research quotes from several books of interpretation in general and more specifically taken from the tafsir book of Taisirul Karim Ar- Rahman fii Tafsir Kalamil Mannan by Imam Abdurrahman Bin Nashir Bin Abdirrahman As-Sa'di. Based on the results of the research, from the disputes that will occur in the community by understanding the promises of Allah Subhanahu Wa Ta'ala and the warnings of Allah Subhanahu Wa Ta'ala that have been mentioned in the Qur'an, and from the stories mentioned in the Qur'an, which of course Ukhuwwah Islamiyyah should be realized in the life of society in general and among Muslims in particular. It should be realized from the point of view of how to make peace in everyday life with good morals, and how to speak words with commendable morals.